Microbial communities and functions changed in rhizosphere soil of Pinus massoniana provenances with different carbon storage - Huang, Zichen; He, Xin; Zhang, Chi; Zhang, Mengyang; Wang, Jiannan; Hou, Yanqing; Wang, Dengbao; Yao, Sheng; Yu, Qiong; Ji, Kongshu (Frontiers in Microbiology, 2023)
The average carbon storage of Pinus massoniana is much higher than the average carbon storage of Chinese forests, an important carbon sink tree species in subtropical regions of China. However, there are few studies on the differences in rhizosphere microorganisms of P. massoniana with different carbon storages. To clarify the relationships between plant carbon storage level, environmental parameters and microbial community structure, we identified three carbon storage levels from different P. massoniana provenances and collected rhizosphere soil samples. We determined chemical properties of soil, extracellular enzyme activity, and microbial community structures at different carbon storage levels and examined how soil factors affect rhizosphere microorganisms under different carbon storage levels. The results revealed that soil organic carbon (SOC), nitrate nitrogen (NO3 --N), ammonium nitrogen (NH4 + -N) contents all increased with increasing carbon storage levels, while pH decreased accordingly. In contrast, the available phosphorus (AP) content did not change significantly. The soil AP content was within the range of 0.91~1.04 mg/kg. The microbial community structure of P. massoniana changed with different carbon storage, with Acidobacteria (44.27%), Proteobacteria (32.57%), and Actinobacteria (13.43%) being the dominant bacterial phyla and Basidiomycota (73.36%) and Ascomycota (24.64%) being the dominant fungal phyla across the three carbon storage levels. Soil fungi were more responsive to carbon storage than bacteria in P.2 massoniana. C/N, NH4 + -N, NO3 --N, and SOC were the main drivers (p < 0.05) of changes in rhizosphere microbial communities. The results revealed that in the rhizosphere there were significant differences in soil carbon cycle and microorganism nutrient preferences at different carbon storages of P. massoniana provenance, which were significantly related to the changes in rhizosphere microbial community structure. Jiangxi Anyuan (AY) provenance is more suitable for the construction of high carbon storage plantation.